2018
DOI: 10.1186/s13287-018-0950-x
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the genic and metabolic characteristics of induced pluripotent stem cells from polycystic ovary syndrome women

Abstract: BackgroundPolycystic ovary syndrome (PCOS) is a common endocrine and metabolic disorder that affects female fertility. However, with the lack of a corresponding research model, the pathology mechanism of PCOS is poorly understood. Induced pluripotent stem cell (iPSC) technology has been recognized as means to generate patient-specific stem cells for disease modeling.MethodsThe mRNA abundance of iPSCs was analyzed by RNA microarray and real-time polymerase chain reaction (RT-PCR). Karyotyping of iPSCs was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Consistent with our study, Min et al. detected increased mtDNA CN and increased expression levels of mtDNA replication-related factors in PCOS-patient-derived induced pluripotent stem cells ( 31 ). This inconsistency may be attributed to participant preferences or the different sample size of the studied population.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our study, Min et al. detected increased mtDNA CN and increased expression levels of mtDNA replication-related factors in PCOS-patient-derived induced pluripotent stem cells ( 31 ). This inconsistency may be attributed to participant preferences or the different sample size of the studied population.…”
Section: Discussionsupporting
confidence: 92%
“…Research has found a correlation between PCOS and other metabolic problems, including high blood pressure, depression and anxiety, dyslipidemia, and chronic inflammation. It has also been verified that metabolic disorders are common in women with PCOS (23). Hang Wun and cols., in their study, stated that vitamin D deficiency was highly prevalent in women with PCOS in Scotland, with this rate having been higher than that of ovulatory control women and the general UK population.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, decreased expression of GLUTs and related mitochondrial dysfunction may be associated with IR in PCOS. Mitochondrial biogenesis may be increased to compensate for the disruption of the functional integrity of mitochondria and the mitochondrial dysfunction of iPSCs from patients with PCOS [88]. In my opinion, these paradoxical results may be induced by different stages of disease manifestation.…”
Section: Pcos and Mitochondrial Genome Abnormalitiesmentioning
confidence: 99%